FORMULATION OF INSTRUCTIONAL AIMS IN TECHNICAL SUBJECTS - KROPAC, Jiri; PLISCHKE, Jitka (Trends in education, 2008)
The article is focused on ways how to reach explicit and controllable instructional aims (principal aims, partial aims). The decision point of the article is the application of Mager extasciiacutes technique of formulation of the aims, which made for our conditions D. Tollingerova, for the instruction of technical subjects.
Keywords: didactics of technical subjects; instructional aims; Mager extasciiacutes technique